Promises, Projects, and Power: Italy and Indonesia Elites in the Belt and Road Initiative - Piasentini, Matteo; Iannone, Aniello (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2025)
This research examines the political and economic dynamics of Italy and Indonesia in relation to their engagement with China's Belt and Road Initiative (BRI). Drawing from the theoretical tradition of state instrumentalism and recent conceptualisations of the “infrastructure state” as an emerging global phenomenon, we argue that initiatives such as the BRI do serve the purposes of political elites in both the developing and developed world. The comparative analysis between the two dissimilar countries, Italy and Indonesia, reveals the existence of a broader global trend. Both experience democratic backsliding while strategically engaging with the BRI to meet their infrastructural needs and political objectives. This study contributes to understanding how domestic political dynamics and external economic opportunities intersect in shaping the developmental trajectories of middle-power states within the global geopolitical landscape.